STRATEGI DAN IMPLEMENTASI PENYUSUNAN SOAL HIGHER ORDER THINGKING SKILS (HOTS BAGI GURU DI SDN 12 PADANGLUA KECAMATAN BANUHAMPU - Yelfianita; Desyandri (STKIP Subang, 2022)
The 2013 curriculum is an element of transformation at the elementary school level. These elements are in the form of strengthening learning, implementing integrated thematic learning, and developing higher order thinking skills through a scientific approach. To make this happen, elementary teachers need to have competence in planning, implementing, and evaluating HOTS learning, but many of them do not understand and apply assessments that measure these higher-order thinking skills. This PKM is expected to be able to provide insight into the understanding of teachers in carrying out learning and evaluating students on higher-order thinking aspects. This PKM is carried out in a group activity forum, teacher work which is held once a week for four meetings. The strategy used is an explanation of the HOTS concept, discussion of developing indicators of basic competencies, workshops on the preparation of grids and rules for writing questions, and preparation of HOTS questions. From the results that have been implemented, it can be concluded that a small proportion of elementary school teachers have carried out HOTS learning and assessments; This activity is able to increase the understanding of teachers' understanding so that it can produce outputs in the form of grids and the development of HOTS questions in thematic learning covering the main areas of Civics, Indonesian Language, Social Sciences, Science, and Mathematics.